The Effectiveness of Regional Regulation Number 19 of 2021 on Beggars and Buskers in Pontianak City - Isdianto; Annisa Rizqa Alamri; Brigida Lusi; Sofia Bagassidi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This study aims to assess the effectiveness of Regional Regulation No. 19 of 2021 in addressing the presence of beggars and buskers in Pontianak. Data sources include primary and secondary data, with analysis guided by Dunn's Evaluation Theory, focusing on five indicators: program understanding, target accuracy, timeliness, goal achievement, and real change. This theory elucidates the nexus between government decision-making and regulation implementation. Data were collected through observation, interviews, and document analysis as part of qualitative descriptive research. Informants, comprising Pontianak City social service employees, buskers, beggars, and community members, were selected using Purposive Sampling. The regulation was instituted in response to the fluctuating numbers of beggars and buskers in Pontianak from 2019 to 2023. Findings indicate a necessity for the regulation to better align with Effectiveness Indicators, notwithstanding commendable progress in actual change indicators. Nonetheless, further enhancements are required for the regulation to achieve optimal effectiveness.